Efficacy and safety of idelalisib in combination with ofatumumab for previously treated chronic lymphocytic leukaemia: an open-label, randomised phase 3 trial. Issue 3 (March 2017) - Jones, Jeffrey A; Robak, Tadeusz; Brown, Jennifer R; Awan, Farrukh T; Badoux, Xavier; Coutre, Steven; Loscertales, Javier; Taylor, Kerry; Vandenberghe, Elisabeth; Wach, Malgorzata; Wagner-Johnston, Nina; Ysebaert, Loic; et al.
Summary: Background: Idelalisib, a selective inhibitor of PI3Kδ, is approved for the treatment of patients with relapsed chronic lymphocytic leukaemia (CLL) in combination with rituximab. We aimed to assess the efficacy and safety of idelalisib in combination with a second-generation anti-CD20 antibody, ofatumumab, in a similar patient population. Methods: In this global, open-label, randomised, controlled phase 3 trial, we enrolled patients with relapsed CLL progressing less than 24 months from last therapy. Patients refractory to ofatumumab were excluded. Patients were stratified by relapsed versus refractory disease, presence or absence of del(17p) or TP53 mutation, or both, and IGHV mutated versus unmutated. We randomised patients in a 2:1 ratio using a web-based interactive system that generated a unique treatment code, and assigned patients to receive either idelalisib plus ofatumumab (oral idelalisib 150 mg twice daily continuously plus ofatumumab 300 mg intravenously in week 1, then 1000 mg intravenously weekly for 7 weeks, and every 4 weeks for 16 weeks) or ofatumumab alone (ofatumumab dosing as per the combination group, except 2000 mg was substituted for the 1000 mg dose). An independent review committee assessed response, including progressive disease, based on imaging using modified International Workshop on Chronic Lymphocytic Leukaemia 2008 criteria. The primary endpoint was progression-free survival assessed by an independent review committee in the intention-to-treat population. We did a primary analysis (data cutoff Jan 15, 2015) and an updated analysis (data cutoff Sept 1, 2015). This trial is registered withClinicaltrials.gov, numberNCT01659021 . Findings: Between Dec 17, 2012, and March 31, 2014, we enrolled 261 patients (median age 68 years [IQR 61–74], median previous therapies three [IQR 2–4]). At the primary analysis, median progression-free survival was 16·3 months (95% CI 13·6–17·8) in the idelalisib plus ofatumumab group and 8·0 months (5·7–8·2) in the ofatumumab group (adjusted hazard ratio [HR] 0·27, 95% CI 0·19–0·39, p<0·0001). The most frequent grade 3 or worse adverse events in the idelalisib plus ofatumumab group were neutropenia (59 [34%] patients vs 14 [16%] in the ofatumumab group), diarrhoea (34 [20%] vs one [1%]), and pneumonia (25 [14%] vs seven [8%]). The most frequent grade 3 or worse adverse events in the ofatumumab group were neutropenia (14 [16%]), pneumonia (seven [8%]), and thrombocytopenia (six [7%] vs 19 [11%] in the idelalisib plus ofatumumab group). Serious infections were more common in the idelalisib plus ofatumumab group and included pneumonia (23 [13%] patients in the idelalisib plus ofatumumab group vs nine [10%] in the ofatumumab group), sepsis (11 [6%] vs one [1%]), and Pneumocystis jirovecii pneumonia (eight [5%] vs one [1%]). 22 treatment-related deaths occurred in the idelalisib plus ofatumumab group (the most common being sepsis, septic shock, viral sepsis, and pneumonia). Six treatment-related deaths occurred in the ofatumumab group (the most common being progressive multifocal leukoencephalopathy and pneumonia). Interpretation: The idelalisib plus ofatumumab combination resulted in better progression-free survival compared with ofatumumab alone in patients with relapsed CLL, including in those with high-risk disease, and thus might represent a new treatment alternative for this patient population. Funding: Gilead Sciences, Inc.